VD_FINDINFO Décision / 2015 / 212 vom 9. März 2015 - VD Tribunal cantonal (2015)
SUPPRESSIONEN GÉNÉRAL, PROCÈS-VERBAL, TROMPERIE, ÉGALITÉ DES ARMES | 140 CPP (CH), 141 CPP (CH), 3 al. 2 let. c CPP (CH), 317 CPP (CH)